2015
DOI: 10.5424/fs/2015243-07545
|View full text |Cite
|
Sign up to set email alerts
|

Taxus globosa Schltdl. (Mexican yew) and Taxus baccata L. (European yew): intra and interspecies analysis of taxol content and biological activity according to different sources

Abstract: Aim of study: Taxus globosa is the only species of Taxus genus that grows in Mexico, and is a tree which is protected by the Mexican Government. This plant shares, with the European species T. baccata, the ability to produce taxanes, such as taxol. The objective of this work was to compare representative samples from two Taxus species: T. globosa Schltdl.("Mexican yew"), and T. baccata L. ("European yew"), by employing different methodological chemical and pharmacological tests.Area of study: Representative sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It has been found that tasumatrol, deacetylbaccatin, paclitaxel and many other terpenoids extracted from Taxus spp. are effective in the anti-inflammatory process initiated through the carrageenan and cotton pellets induced edema model [ 21 , 22 ]. Kyung-Jae Cha.…”
Section: Conifers Extracts Rich In Phytochemical With Putative Health Effectsmentioning
confidence: 99%
“…It has been found that tasumatrol, deacetylbaccatin, paclitaxel and many other terpenoids extracted from Taxus spp. are effective in the anti-inflammatory process initiated through the carrageenan and cotton pellets induced edema model [ 21 , 22 ]. Kyung-Jae Cha.…”
Section: Conifers Extracts Rich In Phytochemical With Putative Health Effectsmentioning
confidence: 99%
“…Yew has evergreen leaves consist of several short, narrow needles with a length of 1 to 2 cm and a width of 1 to 2 mm [5]. Furthermore, the male cones appear in the axils of the leaves; which are globose with 6-14 peltate scales, each with 4-8 pollen sacs [6]. There have been many observations of poisoning due to the ingestion of yew in animals and humans, and the identification of its constituents can help to a better understanding the toxicity and poisoning of this species [7,8].…”
Section: Introductionmentioning
confidence: 99%